2021
DOI: 10.1186/s42234-021-00078-4
|View full text |Cite
|
Sign up to set email alerts
|

Using multielectrode arrays to investigate neurodegenerative effects of the amyloid-beta peptide

Abstract: Background Multielectrode arrays are widely used to analyze the effects of potentially toxic compounds, as well as to evaluate neuroprotective agents upon the activity of neural networks in short- and long-term cultures. Multielectrode arrays provide a way of non-destructive analysis of spontaneous and evoked neuronal activity, allowing to model neurodegenerative diseases in vitro. Here, we provide an overview on how these devices are currently used in research on the amyloid-β peptide and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…MEAs provides a non-invasive method to record electrical signals from whole neuronal networks to underlie the electrical connections between neurons and explore their functionality. Examples of applications of MEAs in bioelectronic medicine include their use to investigate neurotoxic compounds in neurodegenerative disease [55]. Remarkable progress has been made recently in the design of integrated CMOS neural probes, with devices that integrate approximately one thousand recording sites and on-chip circuitry for signal conditioning and digitization with the aim of single-neuron spatial precision and millisecond timing resolution [56,57].…”
Section: Sensing In the Central Nervous Systemmentioning
confidence: 99%
“…MEAs provides a non-invasive method to record electrical signals from whole neuronal networks to underlie the electrical connections between neurons and explore their functionality. Examples of applications of MEAs in bioelectronic medicine include their use to investigate neurotoxic compounds in neurodegenerative disease [55]. Remarkable progress has been made recently in the design of integrated CMOS neural probes, with devices that integrate approximately one thousand recording sites and on-chip circuitry for signal conditioning and digitization with the aim of single-neuron spatial precision and millisecond timing resolution [56,57].…”
Section: Sensing In the Central Nervous Systemmentioning
confidence: 99%
“…Although a study using a MEA system allowed to characterize the spatial properties of oscillating electrical activity in ex vivo mouse ileum, the data collected did not provide a fine analysis of enteric neuronal networks, but rather an overview of a cellular cooperation including muscle, neuronal and interstitial cells (Taniguchi et al, 2013). Finally, a second study recently reported the application of myenteric neuron cultures in MEA chips but without presenting the corresponding recordings (Schulte et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The recording of multiple neurons in close proximity has been attempted using the paired clamping or multielectrode arrays (MEA), however, it was difficult to measure the activity pattern of neural networks. With the advent of high density multielectrode arrays (HD MEA), thousands of neurons can be recorded simultaneously down to the subcellular level, allowing for the construction of a functional connectivity map (Ito et al 2014; Miccoli et al 2019; Schulte et al 2021). By using HD MEA, we are able to detect changes in network activity both in primary neuron cultures and in brain slices.…”
Section: Introductionmentioning
confidence: 99%